Examining the quality of name code record linkage: what is the impact on death and cancer risk estimates? A validation study. (7th November 2014) - Swart, Alexander; Meagher, Nicola S.; van Leeuwen, Marina T.; Zhao, Kun; Grulich, Andrew; Mao, Limin; Randall, Deborah Anne; Degenhardt, Louisa; Burns, Lucy; O'Connell, Dianne; Amin, Janaki; Vajdic, Claire M.
Abstract Objective: To examine the validity and impact of record linkage using name code compared to full name records. Methods: A registry of 45, 419 opioid substitution clients (1985–2007) was linked with national population‐based death and cancer registries using registrant's name, date of birth, sex, state, postcode and date of death. Records were linked using full name and then using the first two letters of the given and surname (2×2 name code). Sensitivity and specificity were computed and regression analysis used to identify factors related to linkage accuracy. Standardised mortality ratios (SMR) and standardised cancer incidence ratios (SIR) were estimated. Results: The sensitivity and specificity of name code compared to full name linkage were 65.31% and 99.91% for death records and 76.81% and 99.89% for cancer records. Registrants' age and sex and accuracy of the registries were associated with risk of false linkages. Death and cancer risks (SMR 6.98, 95%CI 6.77–7.19; SIR 1.16, 95%CI 1.08–1.24) were significantly under‐estimated using name code linkage (SMR 4.39, 95%CI 4.23–4.56; SIR 0.92, 95%CI 0.85–0.99). Conclusion: Record linkage using 2×2 name code has low sensitivity but high specificity, resulting in conservative estimates of death and cancer risk. This may translate to meaningful differences in outcomes.